Risk factors for depression in elderly diabetic patients and the effect of metformin on the condition - Fenqin Chen; Guozhu Wei; Yingfang Wang; Tingting Liu; Ting Huang; Qian Wei; Guojing Ma; Difei Wang (BMC Public Health, 2019)
Abstract Background At present, only a few studies have focused on the risk factors for depression in elderly diabetic patients, and there is little evidence for the effect of metformin in depressed elderly patients with diabetes than on its effect on blood glucose. The aim of the current work was to study the risk factors for depression in elderly diabetic patients and to ascertain the effects of metformin on the depressive state. Methods We initiated a 1:4 matched case–control study. The case group comprised 110 elderly diabetic patients with depression from nine communities in Shenyang in 2017. The control group comprised 440 non-depressed elderly diabetic patients from the same communities, which were matched by gender and age (± 2 years of age) with the case group. Depression was measured using the Geriatric Depression Scale-15, and we performed matched univariate and multivariate logistic regression analyses. Results In the multivariate analysis, overweight status, poor physical capabilities and low activity level, and the presence of more than two additional illnesses were risk factors for depression in elderly patients with diabetes. For these risk factors, the adjusted ORs (all P < 0.05) were as follows: an adjusted OR of 2.031 and 95% CI of 1.180–3.495; an adjusted OR of 2.342 and 95% CI of 1.465–3.743; and an adjusted OR of 5.350 and 95% CI of 2.222–12.883, respectively. Patients taking metformin had a lower risk of depression than those taking no medication, with an adjusted OR of 0.567 and 95% CI of 0.323–0.997 (P < 0.05). Conclusions Overweight status, poor physical capabilities and low activity level, and the presence of more than two additional illnesses were risk factors for depression in elderly diabetic patients, and metformin was a protective factor against depression in elderly diabetic patients.